2007
DOI: 10.1080/10428190601186143
|View full text |Cite
|
Sign up to set email alerts
|

Tetra-O-methyl nordihydroguaiaretic acid inhibits growth and induces death of leukemia cells independent of Cdc2 and survivin

Abstract: Tetra-O-methyl nordihydroguaiaretic acid (M4N) was shown to induce G2 arrest and suppress human xenograft tumor growth by inhibiting Cdc2 and survivin. We examined the effect of M4N on leukemia and found that M4N inhibited growth and induced cell death in leukemic cell lines and blasts from AML patients. However, no significant changes in Cdc2 and survivin levels and G2 arrest were observed. Cell death and growth inhibition were dependent neither on XIAP, Bcl-2, and Bcl-X(L) levels nor on caspase-8. M4N did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Since primary tumor cultures are believed to reflect more accurately the in vivo tumors than established cancer cell lines [24,38], we considered highlighted the anti-growth capacity of M4N on these cells. Growth inhibitory effects of M4N on cancer cells lines and various kinds of xenograft tumors have been reported elsewhere [39][40][41][42][43][44][45]. Our study indicates that GBM is an additional promising target of the M4N therapy.…”
Section: Discussionsupporting
confidence: 77%
“…Since primary tumor cultures are believed to reflect more accurately the in vivo tumors than established cancer cell lines [24,38], we considered highlighted the anti-growth capacity of M4N on these cells. Growth inhibitory effects of M4N on cancer cells lines and various kinds of xenograft tumors have been reported elsewhere [39][40][41][42][43][44][45]. Our study indicates that GBM is an additional promising target of the M4N therapy.…”
Section: Discussionsupporting
confidence: 77%
“…NDGA, along with the extract from the fungus Lecanicillum lecanii, inhibits the growth of lymphatic leukemia cells by inducing nuclear damage leading to reduced DNA content in the cells (Bibikova et al, 2017). Besides, the compound causes cell death in AML cell lines as well as in patient samples via inhibition of AKT phosphorylation, suggesting that the extrinsic and the mitochondrial apoptotic pathways are not essential for cell death (Mak et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Mak et al demonstrated a similar phenomenon in leukemic cells. Administration of 0–40µM terameprocol promoted cell death but failed to result in suppression of survivin or Cdk1 expression [34]. …”
Section: Discussionmentioning
confidence: 99%